Mouse model as an efficacy test for foot‐and‐mouth disease vaccines. Issue 6 (15th May 2020) - Gnazzo, Victoria; Quattrocchi, Valeria; Soria, Ivana; Pereyra, Erica; Langellotti, Cecilia; Pedemonte, Andrea; Lopez, Virginia; Marangunich, Laura; Zamorano, Patricia
Abstract: Protection against foot‐and‐mouth disease virus (FMDV) has been linked to the development of a humoral response. In Argentina, the official control tests for assessing the potency of FMD vaccines are protection against podal generalization (PPG) and expected percentage of protection (EPP) curves built with quantitative data of antibodies determined by liquid‐phase blocking ELISA (lpELISA). The results of these tests are used to accept or discard vaccines at the batch level. In this report, a mouse model was assessed as an alternative efficacy control for FMDV vaccines. To this aim, groups of cattle ( n  = 18) and BALB/c mice ( n  = 16) were inoculated with commercial FMDV vaccines and bleedings were performed 60 days post vaccination (dpv) in cattle and 21 dpv in mice. Specific FMDV antibody titres were measured in both species by a standardized lpELISA. A statistically significant association between antibody levels in cattle and mice has already been demonstrated. However, some vaccines have been misclassified since they were considered protective based on lpELISA results but did not induce good protection in cattle upon challenge. For this reason, other immunological parameters were evaluated to improve the prediction of protection in mice, without the need of using infective virus. In addition, antibody titres by lpELISA, the IgG2b/IgG1 isotype ratio and the Avidity Index were identified as good predictors, resulting in an optimal predictive model of protection. This mouse model could be a simple and economic alternative for testing FMD vaccines since the disadvantages of high costs and facility requirements associated with the use of large animals are overcome.